A novel genetic engineering platform for the effective management of biological contaminants for the production of microalgae. Issue 10 (28th May 2016) - Loera‐Quezada, Maribel M.; Leyva‐González, Marco Antonio; Velázquez‐Juárez, Gilberto; Sanchez‐Calderón, Lenin; Do Nascimento, Mauro; López‐Arredondo, Damar; Herrera‐Estrella, Luis
Summary: Microalgal cultivation that takes advantage of solar energy is one of the most cost‐effective systems for the biotechnological production of biofuels, and a range of high value products, including pharmaceuticals, fertilizers and feed. However, one of the main constraints for the cultivation of microalgae is the potential contamination with biological pollutants, such as bacteria, fungi, zooplankton or other undesirable microalgae. In closed bioreactors, the control of contamination requires the sterilization of the media, containers and all materials, which increases the cost of production, whereas open pond systems severely limits the number of species that can be cultivated under extreme environmental conditions to prevent contaminations. Here, we report the metabolic engineering of Chlamydomonas reinhardtii to use phosphite as its sole phosphorus source by expressing the ptxD gene from Pseudomonas stutzeri WM88, which encodes a phosphite oxidoreductase able to oxidize phosphite into phosphate using NAD as a cofactor. Engineered C. reinhardtii lines are capable of becoming the dominant species in a mixed culture when fertilized with phosphite as a sole phosphorus source. Our results represent a new platform for the production of microalgae, potentially useful for both closed photobioreactors and open pond systems without the need for using sterile conditions nor antibiotics or herbicides to prevent contamination with biological pollutants.